Nonlinear creep damage model of rock considering alkali solution corrosion - Wenbo Liu; Shuguang Zhang; Xiang Huang; Jiaming Li (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract In order to accurately describe the characteristics of each stage of triaxial creep behavior of rock in alkaline environment, the graded loading creep tests are carried out under the chemical corrosion of NaOH solution with different concentrations and pH values. The microscopic pore structure, porosity and phase composition of rocks immersed in different pH solutions are tested. The rock microstructure characteristics of solutions with different pH values are obtained. Based on the damage degradation law of cohesion and internal friction angle and chemical damage theory, a nonlinear creep damage model of rock considering alkali solution corrosion is established. The results show that with the increase of pH value, the porosity shows a gradual upward trend. This indicates that the pore structure of sandstone may change in an alkaline enhanced environment. This leads to the expansion of pore size or the formation of new pores. In the neutral environment, the rock skeleton structure is partially loose. But no obvious cracks and pores appear. In the alkaline environment, some pores and cracks appear. With the increase of pH value, the loss of rock mineral particles is more obvious. The derived constitutive model can well describe the characteristics of each stage of the triaxial creep behavior of rock under the corrosion of alkaline solution. The model can more accurately capture the changes of rock creep characteristics caused by these changes and thus more accurately reflect the creep behavior of rock under actual working conditions. The Nishihara model is relatively traditional. It does not fully consider the influence of the specific factor of alkali solution corrosion, and cannot accurately describe the complex mechanical response of rock after alkali solution corrosion. The research results provide a theoretical basis for further study on the long-term stability of rock engineering under multi-field coupling.